2023
DOI: 10.1021/acs.jpclett.2c03373
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Intrinsic Hole Trapping and Its Amplitude Variation in a Highly Photoluminescent Toxic-Metal-Free Quantum Dot

Abstract: Intrinsic hole trapping as well as hole detrapping have not been observed for any quantum dot (QD) or perovskite nanocrystal (PNC) system. Moreover, amplitude variation of intrinsic hole trapping (or detrapping) has not been reported at all for any QD or PNC system. However, for a CuInS2-based core/alloy-shell (CAS) QD system, (a) both intrinsic hole trapping and detrapping have been observed and (b) very significant amplitude variations of hole trapping (∼16 to ∼42%) and hole detrapping (∼44 to 23%) have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The higher peak value of the distributions of ON fraction for PNC1 in comparison to PNC2 corroborates well with the higher PLQY of the host band for PNC1. 8,10,11,28–35 These SPS-based observations point to the fact that because of Mn doping (the host band of) PNC2 spends more time in the OFF state in comparison to undoped PNC, i.e. PNC1.…”
Section: Resultsmentioning
confidence: 99%
“…The higher peak value of the distributions of ON fraction for PNC1 in comparison to PNC2 corroborates well with the higher PLQY of the host band for PNC1. 8,10,11,28–35 These SPS-based observations point to the fact that because of Mn doping (the host band of) PNC2 spends more time in the OFF state in comparison to undoped PNC, i.e. PNC1.…”
Section: Resultsmentioning
confidence: 99%
“…8A). [66][67][68][69][70][71][72][73] Photoluminescence excitation (PLE) measurements were used to reveal excitation energydependent (EED) PLQYs, which were first shown by Hoheisel et al 66 These measurements showed a monotonic drop in CdSe NC PLQY when ensembles were stimulated to the blue of their band edge. The reason for this decrease is explained as particles being excited into a range of states that differed from constrained NC states.…”
Section: Excitation Energy-dependent Quantum Yieldmentioning
confidence: 99%
“…71 Nonetheless, it has been discovered that sometimes hole trapping can be beneficial for increasing the PLQY for CuInS 2 -based core/alloy-shell CQDs while maintaining the same EED PLQY trend. 72 Regarding EED PLQYs, there is conflicting evidence suggesting that they might be artifacts resulting from measurement mistakes. According to Tonti et al, EED PLQYs are caused by excess surface ligands and NC aggregates in the solution.…”
Section: Excitation Energy-dependent Quantum Yieldmentioning
confidence: 99%
“…PLQY of core–shell CIS QDs can be as high as 80–96%. , However, in contrast to the narrow emission profiles of band edge emitting materials such as CdSe, CIS QDs exhibit a large Stokes shift and a relatively broad emission band, suggesting a significant contribution from intraband defect recombination pathways. ,,, In addition, for larger CIS nanoparticles approaching the Bohr exciton radius, the long wavelength side of the photoluminescence (PL) spectral peak extends further than that allowed by a band edge transition in the bulk material. Furthermore, the PLQY of Cu-deficient CIS QDs, with their associated high density of copper vacancy defects, is greater than that of an equivalent stoichiometric sample, , indicating that defects play a significant role in CIS QD emission.…”
Section: Introductionmentioning
confidence: 99%